THE IMPORTANCE OF INTERCULTURAL SENSITIVITY (Academicia Globe: Inderscience Research, 2024)
The article discusses the concept of intercultural sensitivity, its significance, and practical ways to develop it. The discussion aims to provide a clear, easy-to-understand explanation suitable for individuals seeking to enhance their cultural competence.